2020
DOI: 10.2967/jnumed.120.255794
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron produced 132La as a PET imaging surrogate of therapeutic 225Ac

Abstract: The aim of this work is to explore 132 La as a PET imaging surrogate of 225 Ac using a DOTA-based, tumor-targeting alkylphosphocholine (NM600). Methods: 132 La was produced on a biomedical cyclotron. For in vivo experiments, mice bearing 4T1 tumors were administered 132 La-NM600, and PET/CT scans were acquired up to 24h post-injection (p.i.). Following the last timepoint, ex vivo tissue distribution was measured to corroborate in vivo PET data. Ex vivo tissue distribution was performed at 4h and 24h p.i. in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…The trio of lanthanum radionuclides 132 La, 133 La and 135 La present an interesting prospect for the fulfilment of the ideal theranostic concept of chemically-identical matching of diagnostic and therapeutic radionuclides (Aluicio-Sarduy et al 2020 ). 132 La (t 1/2 = 4.6 h) is a positron emitter that has garnered interest as a PET imaging radionuclide and has seen applications as a surrogate imaging agent to probe the in vivo biodistribution of 225 Ac due to similarities in their chemical properties (Aluicio-Sarduy et al 2021 ). Likewise, the positron emitter 133 La has also emerged as a PET imaging candidate with the potential to improve the PET imaging quality of metastases and smaller tumours.…”
Section: Lanthanum: 132 La ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The trio of lanthanum radionuclides 132 La, 133 La and 135 La present an interesting prospect for the fulfilment of the ideal theranostic concept of chemically-identical matching of diagnostic and therapeutic radionuclides (Aluicio-Sarduy et al 2020 ). 132 La (t 1/2 = 4.6 h) is a positron emitter that has garnered interest as a PET imaging radionuclide and has seen applications as a surrogate imaging agent to probe the in vivo biodistribution of 225 Ac due to similarities in their chemical properties (Aluicio-Sarduy et al 2021 ). Likewise, the positron emitter 133 La has also emerged as a PET imaging candidate with the potential to improve the PET imaging quality of metastases and smaller tumours.…”
Section: Lanthanum: 132 La ...mentioning
confidence: 99%
“…Cyclotrons have also been used for the production of 132 La from natural Ba targets via the 132 Ba(p,n) 132 La chemical reaction, in a similar manner to the production of 135 La, for the production of the theranostically relevant 132 La/ 135 La radionuclide pair (Aluicio-Sarduy et al 2021 , 2019 ). However, it has been reported that current production routes to 132 La using natural Ba targets have been hindered by current cyclotron production methods requiring long irradiation times and the relatively low natural abundance of the requisite 132 Ba isotope (0.1% natural abundance) (Nelson et al 2020 ).…”
Section: Lanthanum: 132 La ...mentioning
confidence: 99%
“…Theranostics has strong potential in targeted radionuclide therapy, where a diagnostic positron or gamma-emitting radionuclide used in PET or SPECT is paired with an alpha (α), beta (β -), or Auger electron-emitting therapeutic radionuclide (2). Recently introduced 133 La (t1/2=3.9 h), 132 La (t1/2=4.8 h), and 134 Ce (t1/2=3.2 d)/ 134 La (t1/2=6.5 min) PET radionuclides are uniquely suited as theranostic imaging partners for 225 Ac (t1/2=9.9 d) in targeted alpha therapy (TAT), or with 135 La (t1/2=19.5 h) in Auger electron therapy (AET) due to their chemical similarity and longer half-lives compared to the ubiquitous PET radiometal 68 Ga (t1/2=68 min) (2)(3)(4)(5)(6)(7). Actinium-225 has shown considerable efficacy in clinical trials for treating metastatic cancers (2,8).…”
Section: Introductionmentioning
confidence: 99%
“…Actinium-225 has shown considerable efficacy in clinical trials for treating metastatic cancers (2,8). Lanthanum-132 has been proposed as a theranostic PET imaging surrogate for 225 Ac therapy, and displayed similar in vivo uptake characteristics compared to 225 Ac (6). However, there are fundamental imaging limitations inherent to 132 La due to its high positron emission energy (Emax/Emean=3.67/1.29 MeV) that significantly reduces image spatial resolution and contrast compared to other PET radionuclides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Production using this class of cyclotron was selected since these machines are the most prevalent in medical and research institutions. While the list of radioisotopes reviewed is a comprehensive one, the authors would like to highlight other PET radioisotopes such as 110m In 12,13 , 152 Tb, 13,14 51 Mn, 15,16 62 Cu 16-18 and 132 La 19,20 which are also available for production on the aforementioned cyclotrons, but were excluded from this review due to limitations. This review briey discusses the biomedical application of each radionuclide while focusing mainly on the specics of its production and purication procedures.…”
Section: Introductionmentioning
confidence: 99%